BHLHB2 controls Bdnf promoter 4 activity and neuronal excitability. - Jiang, X; Tian, F; Du, Y; Copeland, N; Jenkins, N; Tessarollo, L; Wu, X; Pan, H; Hu, X; Xu, K; Kenney, H; Egan, SE; et al. (2008)
Brain-derived neurotrophic factor (BDNF), via activation of TrkB receptors, mediates vital physiological functions in the brain, ranging from neuronal survival to synaptic plasticity, and has been implicated in the pathophysiology of neurodegenerative disorders. Although transcriptional regulation of the BDNF gene (Bdnf) has been extensively studied, much remains to be understood. We discovered a sequence within Bdnf promoter 4 that binds the basic helix-loop-helix protein BHLHB2 and is a target for BHLHB2-mediated transcriptional repression. NMDA receptor activation de-repressed promoter 4-mediated transcription and correlated with reduced occupancy of the promoter by BHLHB2 in cultured hippocampal neurons. Bhlhb2 gene -/- mice showed increased hippocampal exon 4-specific Bdnf mRNA levels compared with +/+ littermates under basal and activity-dependent conditions. Bhlhb2 knock-out mice also showed increased status epilepticus susceptibility, suggesting that BHLHB2 alters neuronal excitability. Together, these results support a role for BHLHB2 as a new modulator of Bdnf transcription and neuronal excitability.